A poesia nos labirintos da metrópole: uma leitura da obra de Chacal - Martins Neta, Gabriela Ribeiro (2017)
This study aims an analysis of the work of Ricardo Chacal considering the relationship between the poetic form and the representation of the city, established in the author’s poetry. This selection was imposed from the reading of Chacal’s complete poetry, a long-living work. One evidenced that the city and the relations with the urban space appear as a possible outliner of his search for an artistic expression. From this perception the hypothesis arose that the several faces of the city makes a promising interpretive entrance of his poetry, forming a trail of understanding of a work that begins in the decade of 1970 and continues until the current days. How that dialogue with the metropolis is built and in what measure it determines the linguistic materiality of the poetry of Chacal were the questions that propelled this study. The corpus of the research is composed of twelve poems: “Hóspede do planeta ” (1972), “Jazidas de titânio em Mato Grosso” (1975), “Na jaula do aparelho” (1983), “A coisa e o nome” (2002), “À rua” (2002), “Cidade” (2002), “Mameluco” (2002), “Ruas” (2002), “CEP 20.000” (2002), “SPO3MA” (2007), “New York” (2007) e “Edificações” (2012). To develop this work, we based ourselves on texts of Viktor Chklovski, Octavio Paz and Viviana Bosi about the poetics; Fernanda Medeiros concerning the Chacal’s critical fortune end poetics; and Renato Cordeiro Gomes about literature and city. This dissertation is divided into three chapters: the first one focuses on the relationship between poetry and city; the second brings artistic references that make up the aesthetic project of the poet; and the third is intended to analyze the corpus